Career derailment: burnout and bullying at the executive level - McCormack, Lynne; Abou-Hamdan, Sleiman; Joseph, Stephen (British Psychological Society, 2017)
Executive derailment refers to unexpected and unwanted changes in the trajectory of an executive career caused either by factors within the person or by organisational factors external to the person, or a combination of both, leading to loss of identity. This phenomenological study explored subjective experiences of four high functioning professionals who had experienced executive derailment. Semi-structured interviews were conducted and data were analysed using Interpretative Phenomenological Analysis (IPA). Results showed four superordinate themes that encapsulated a trajectory from severe loss of identity, integrity, and livelihood, to newly defined authenticity following derailment: (1) Self-doubt and blame; (2) targeted bullying; (3) psychological vulnerability and distress; and (4) Meaning-making and personal growth. The first three themes highlight varying levels of psychological distress and burnout and the vicarious impact on family life. The fourth theme involved a redefined self-integrity where forgiveness and psychological recovery could emerge and allow for a reconsideration of career pathways. The recognition that personal and professional growth can arise following executive derailment is a novel finding with important implications for coaches. A positive psychological and growth-oriented mindset may be helpful in harnessing change with executives following derailment.